Correlation between Therapeutic Efficacy of CD34+ Cell Treatment and Directed In Vivo Angiogenesis in Patients with End-Stage Diffuse Coronary Artery Disease - Tien-Hung Huang; Cheuk-Kwan Sun; Yi-Ling Chen; Pei-Hsun Sung; Chi-Hsiang Chu; Mel S. Lee; Yuan-Ping Lin; Hon-Kan Yip; Fan-Yen Lee (Stem Cells International)
Background. This study was aimed at testing the association between the therapeutic efficacy of CD34+ cell treatment in patients with end-stage diffuse coronary artery disease as reflected in angiographic grading and results of directed in vivo angiogenesis assay (DIVAA) on their isolated peripheral blood mononuclear cell- (PBMC-) derived endothelial progenitor cells (EPCs). Methods. Angiographic grades (0: <5%; 1: 5–35%; 2: 35–75%; 3: >75%) which presented the improvement of vessel density pre- and post-CD34+ treatment were given to 30 patients with end-stage diffuse coronary artery disease having received CD34+ cell treatment. The patients were categorized into low-score group (angiographic grade 0 or 1, n=12) and high-score group (angiographic grade 2 or 3, n=18). The percentages of circulating EPCs with KDR+/CD34+/CD45−, CD133+/CD34+/CD45−, and CD34+ were determined in each patient using flow cytometry. PBMC-derived EPCs from all patients were subjected to DIVAA through a 14-day implantation in nude mice. The DIVAA ratio (i.e., mean fluorescent units in angioreactors with EPCs/mean fluorescent units in angioreactors without EPCs) was obtained for each animal with implanted EPCs from each patient. Results and Conclusions. The number of EPCs showed no significant difference among the two groups. The DIVAA ratio in the high-score group was significantly higher than that in the low-score group (p=0.0178). Logistic regression revealed a significant association between the DIVAA ratio and angiographic grading (OR 3.12, 95% CI: 1.14–8.55, p=0.027). The area under the ROC curve (AUC) was 0.8519 (p=0.0013). We proposed that DIVAA may be a reliable tool for assessing coronary vascularization after CD34+ cell treatment.